Novel multifunctional hybrid diallyl ether monomer via azide alkyne click reaction as crosslinking agent in protective coatings. (7th April 2015) - Sykam, Kesavarao; Donempudi, Shailaja
Abstract: Functionalized hybrid monomers with crosslinking ability can provide advantages over the other monomers due to the flexibility of using it with any vinylic family of monomers. Azide alkyne click reaction is a convenient way of introducing triazole moieties into a molecule and opens up the possibility to add more functionality by suitable design of azide and alkyne compounds. In the present study, we report synthesis and use of new azide click linker containing allyl ether functionality, (3-(2-azidoethoxy) prop-1-ene) as a first example in the click reaction with a siloxane functionalized dialkyne to make a novel triazole, siloxane functionalized diallyl ether (TSDE) monomer. Chemical structure of the as synthesized TSDE, azide click linker and other compounds were characterized by FT-IR, 1 H NMR, 13 C NMR, and ESI-MS techniques. Hybrid coatings of TSDE with methyl methacrylate (MMA) were evaluated for chemical structure, morphology, wettability, tensile and thermal properties by FTIR, XRD, SEM, UTM, WCA, DSC & TGA. Experimental results from EPS and fog tests indicate significant enhancements in the anticorrosion and antibacterial performance of the as synthesized new Poly (MMA-co-TSDE) hybrid coatings in comparison to PMMA. Graphical abstract: Highlights: A new hybrid diallyl ether crosslinking monomer (TSDE) was synthesized. Synthesis of a novel allyl ether functional azide clicklinker for the first time. It helps insert inorganic moiety into polymer network through covalent bonding. TSDE provides synergistic benefits to coatings even at low volumes.